Kajian Filologis Naskah Batak Panuratan Ni Poda Aji Mangalo Musu - Hidayani, Fika; Pinem, Desy Natalia; Ladyanna, Sonezza (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2021)
Batak manuscript entitled Panuratan Ni Poda Aji Mangalo Musu is unique in its existence. Beside this manuscript was found only one, the text in it contains the word basmallah. The word basmallah was found in the word of mantra. This is show occurred religious acculturation of the Batak tribe when this manuscript was made.  The manuscript, totally 76 pages, was written in Batak Toba script and language. Because there is only one manuscript, so it uses the diplomatic method in editing the script. This manuscript contains spells to protect oneself from enemies in the environment around the place of residence or outside the area of residence, as well as knowledge about the culture of the Batak people, such as habits in determining good and bad days, how to reject reinforcements, astrology predictions, and  how to shoot the enemy well (mamodil).